(3GdCOdI GdQSejI aj GdJYGHi GdMQHjIs - (3GHf efcdj , eMeO Hf efcdj GdfGUQj,J (B770 (3g` s
(3ChdgG (B:s
(3CeG HYO abO GSJNQJ Gddg JYGdi ai JCdja gPG GdcJGH GdeSei HGdCOdI GdQSejI ai GdJYGHi GdMQHjI s
(3BNQgG (B:s
(3hGdQGYi jSCd cd hGba Ydi gPg GdQSGdI EPG QCi NddkG adjUdMg hgh MSHi hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B112 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B8s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs